2021
DOI: 10.1007/s00520-021-06048-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of benzydamine in prevention and treatment of chemoradiotherapy-induced mucositis

Abstract: Purpose To discuss the role of benzydamine in the prevention and treatment of radiation-induced oral mucositis (OM) in head and neck (H&N) cancer patients. This document represents an expert opinion paper on indications and key-role aspects in OM pathogenesis, prevention and treatment. Oral mucositis OM represents a common side effect of chemotherapy (CHT) and radiotherapy (RT). It consists in a painful erythema involving the oral cavity mucosa, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
2
18
0
2
Order By: Relevance
“…Understanding the involvement of cytokines in the etiology of RIOM may aid in the development of management methods. The proinflammatory cytokines TNFα and IL-6 have been examined and done in multiple studies, all of which have shown an elevation in TNF-a and IL-6 levels [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the involvement of cytokines in the etiology of RIOM may aid in the development of management methods. The proinflammatory cytokines TNFα and IL-6 have been examined and done in multiple studies, all of which have shown an elevation in TNF-a and IL-6 levels [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…3,[21][22][23] A variety of methods have been tried for the prevention or treatment of mucositis, including ice chips, glutamine and N-acetylcysteine, benzydamine hydrochloride, benzydamine hydrochloride, luteolin, peptides, and prostaglandin E1and E2, but none has proven benefits in patients receiving prolonged infusions of HDMTX. 3,9,10,24,25 Some authors declared that Palifermin, a recombinant human keratinocyte growth factor that stimulates growth of epithelial cells, could reduce the incidence of mucositis, but no agreement has been reached on the standardized interventions till now. 3,9 When mucositis occurred, clinicians in our hospital choose to modify the dosing of leucovorin to minimize the side effects, but there is a lag behind adverse reactions, the ongoing cellular damage can cause secondary infection and result in longer stays of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Diverse methods have been tried to prevent or treat mucositis, but no good intervention has proven beneficial in patients receiving continuous infusions of HDMTX. [7][8][9][10][11] Due to the immature immune systems, children are more susceptible to bacteria, viruses or other microbe infections than the adults. 12 Identification of the risk factors involving adverse drug reactions can contribute to the individualization of HDMTX, and to improving therapeutic safety without compromising the anticancer effect.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Benzydamine hydrochloride (Benz) is a well-known non-steroidal anti-inflammatory drug with an antimicrobial effect, along with analgesic and anesthetic ones [24]. It can be applied both locally and systemically, but it influences mostly oral conditions such as ulcers [24], mucositis [25], and postoperative sore throat [26].…”
Section: Introductionmentioning
confidence: 99%